Teknologi Pemanfaatan ASBUTON Sebagai Bahan Perkerasan Jalan - I Ketut Darsana (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Asbuton founded in 1920’s and has been using as pavement material since then, approximately 3.5 million ton. Performance of conventional mixing of Asbuton’s aggregate as Lasbutag was not successful. Therefore, in this paper will be try to find the better solution of Asbuton mix to solve all the boundaries problem. And finding that Teknobutas as the last product, is better comparing with others, and also informed, the last refined of Asbuton.